2018
DOI: 10.1016/j.toxrep.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking and smoking cessation on levels of urinary 11-dehydro thromboxane B2

Abstract: BackgroundThromboxane is a key clinical risk endpoint of smoking-induced inflammation which has been associated in the pathogenesis of cardiovascular disease. The goal of this review is to quantify the effect of smoking and smoking cessation on one of its urinary metabolites, 11-dehydrothromboxaneB2.MethodsPubMed and SCOPUS were searched to identify publications which report urinary 11-dehydrothromboxaneB2 levels in smokers and non-smokers, as well as articles reporting the effect of smoking cessation on urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…The levels of some eicosanoids are known to increase in smokers, most likely due to smoking-induced oxidative stress, and their levels are reported to decrease upon smoking abstinence. Several studies have shown that smokers exhibit higher urinary levels of the AA metabolites LTE 4 , 8-iso PGF 2α , 2,3-d-TXB 2 and 11-dehydrothromboxane B 2 (11-dh-TXB 2 ) compared to non-smokers or users of moist snuff [ 11 , 14 , 30 ]. In the current study, significant reductions in 8-iso PGF 2α levels were observed in only the younger age cohort at both 7 and 14 days of smoking abstinence (36% and 29%, respectively; Supplementary Scheme S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of some eicosanoids are known to increase in smokers, most likely due to smoking-induced oxidative stress, and their levels are reported to decrease upon smoking abstinence. Several studies have shown that smokers exhibit higher urinary levels of the AA metabolites LTE 4 , 8-iso PGF 2α , 2,3-d-TXB 2 and 11-dehydrothromboxane B 2 (11-dh-TXB 2 ) compared to non-smokers or users of moist snuff [ 11 , 14 , 30 ]. In the current study, significant reductions in 8-iso PGF 2α levels were observed in only the younger age cohort at both 7 and 14 days of smoking abstinence (36% and 29%, respectively; Supplementary Scheme S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that levels of 11-dh-TXB 2 are also higher in smokers compared to non-smokers (including moist snuff users) [ 12 , 13 , 14 ]. A meta-analysis [ 11 ] confirmed a higher urinary excretion of 11-dh-TXB 2 in smokers compared to non-smokers, and also discussed several cessation studies that reported a rapid decline in the urinary levels of 11-dh-TXB 2 . For example, 2,3-d-TXB 2 and 11-dh-TXB 2 declined by three days in women ( n = 8) who quit smoking [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation